Dietary silymarin supplementation enhances chemotherapy efficacy of capecitabine and irinotecan and mitigates hepatotoxicity in a mouse model of colon cancer - Sepideh Hassani; Hassan Malekinejad; Mohammad Hassan Khadem-Ansari; Ata Abbasi; Fatemeh Kheradmand (Research in Pharmaceutical Sciences)
Background and purpose: The flavonoid silymarin (SMN) has shown promise due to its antioxidant, anti-inflammatory, and anticancer properties. SMN has been widely used in preclinical and clinical studies to treat various types of cancer, alone and with chemotherapy agents. Recent research suggests that SMN may increase conventional chemotherapy efficacy and reduce adverse effects. Herein, we investigated the therapeutic efficacy of SMN and its combination with capecitabine (CAP) and irinotecan (IRI) in a mouse model of colon cancer. Experimental approach: Following 1,2 dimethylhydrazine-induced colon cancer, a modified diet supplemented with SMN (2500 ppm) and mono- and combined therapy of CAP and IRI was used. Serum samples were analyzed for lipid profile, liver function, and inflammatory cytokines. Oxidative stress and inflammation markers, including malondialdehyde (MDA), nitric oxide (NO), myeloperoxidase (MPO), superoxide dismutase (SOD), and glutathione peroxidase (GPx) were measured in colonic, hepatic, and circulatory samples. Colonic BAX and Bcl-2 levels were examined via western blotting and histopathological analysis of colon sections was conducted. Findings/Results: SMN alone and combined with chemotherapeutic agents significantly mitigated the elevated inflammatory cytokines liver function enzyme levels, and hyperlipidemia. Furthermore, SMN supplementation with chemotherapy agents enhanced antioxidant activity and reduced lipid peroxidation and inflammatory markers. Significant upregulation of BAX and downregulation of Bcl-2 were observed. In addition, treatment regimens ameliorated carcinogen-induced polyp multiplicity, adenoma formation, dysplastic changes, and lymphocytic aggregation. Conclusion and implications: Our results demonstrated that the potential anticancer properties of SMN could enhance chemotherapy efficacy and reduce carcinogen- and chemotherapy-induced hepatotoxicity.